New political elite : inconsequential MP? - Vohra, Guatam (Delhi, 1994)
Some MPs are more equal than others. A truism that is applicable to all walks of life, but more so in relation to our man in Parliament. But even the high profile MP enjoys hardly any power as a legislator. As a member of various parliamentary committees he may, or may not, influence policy, but there is little doubt that these do not enjoy the clout they did during the Nehru era. By contributing to debates in the House, the MP of the fifties could be said to have had pact on policy, but this is hardly the case today. The speeches that cover a wide range of issues (and given considerable space in this volume) are often no more than routine affairs in support of the party position, adding nothing or little of substance to the subject under discussion. As for the questions raised by the MP, he is fobbed of, more often than not, by replies that conceal more than they reveal, replies drafted hurriedly by the bureaucrat to ensure that his boss does not get embroiled in any controversy. Hence the only job left to him is to tackle the demands of his voters. In doing so he is often stepping on the toes of the MLA or the municipal councillor. As things are, he is not as well placed to deliver the goods as them. He has, in effect, no role to play. It is in this context that the author has posed the question in the title of the book, asking whether the new MP, the MP of the nineties, is of any consequence.
Volume 2 : Gautam Vohra
Keywords: Political elite